Роль фразеологічних одиниць у художніх і наукових текстах Агатангела Кримського - Стельмах, Богдана Володимирівна; Stelmakh, Bohdana (Східноєвропейський національний університет, 2013)
У статті йдеться про взаємозв’язок національно-мовної картини світу із мовною картиною світу індивіда, що виявляється, зокрема, у використанні А. Кримським в авторській та перекладній поезії, прозових творах і наукових текстах фразеологічних одиниць. The article tells about relationship of the national language world with the language world of the individual, which is, in particular, the use of Agatangel Krymskiy author works and translations poetry, prose texts and scientific texts of phraseological units. This is due to the fact that human behavior, perception of the world around him is based on the experience of generations - some stereotypes that are verbally in the language of each individual. Having used an traditional and transformed phraseological units, A. Krimskiy, therefore, not only filled the works of figurative coloring, deep emotion, but also showed their affiliation with the people, their spiritual roots and at the same time, gave his vision and perception of certain facts, events, gave his assessment of the that depicts, his state of mind.
The Role of Phraseological Units in Artistic and Scientific Texts of Agatangel Krymskiy
Keywords: мовна картина світу; індивід; фразеологічні одиниці; художній твір; науковий текст; linguistic world picture; individual; phraseological units; artistic text; scientific text